Labour market dynamics in Germany: Hirings, separations, and job-to-job transitions over the business cycle - Ronald Bachmann (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
In this paper, we provide a comprehensive overview of labour market dynamics in Western Ger- many by looking at gross worker flows. To do so, we use a subsample of the registry data collected by the German social security system, the IAB employment sample, for the time period 1975-2001. The latter provides daily information on 2% of the German workforce covered by social security legislation. Using these data, we are able to exactly calculate the number of transitions between the different labour market states, and between different employers over time. We first provide an overview of the cross-section and time series properties of these flows. We then study the cyclical features of gross worker flows, accessions, and separations. We find that separations are relatively flat over the cycle, while accessions are markedly procyclical, and that the increased flow into unemployment in a recession is mainly due to reduced hirings, and hence lower job-to-job transitions, rather than increased match separations. Our findings have important implications both for the way we view recessions and for the role of the labour market as a propagation mechanism for productivity shocks.
Keywords: J63; J64; J21; E24; 330; worker flows; accessions; separations; business cycle; job-to-job; employer-to-employer